Urban Scenic Spot Activity Center Investment: Strategic Construction Company Selection Using the Grey System-II Thinking Compromise Ranking of Alternatives from Distance to Ideal Solution Multi-Criteria Decision-Making Method - Shuo Zhang; Moses Olabhele Esangbedo (Systems)
Investing in urban scenic spots is a complex process that requires careful consideration of multiple criteria to ensure sustainability and efficiency. In the post-pandemic era, the uncertainty of future trends necessitates effective risk management and informed investment decisions. Revitalizing urban scenic spots while maintaining profitability, along with the construction of multi-purpose activity centers, requires a thorough evaluation of construction companies. This study addresses the selection of the most suitable contractor for constructing multi-purpose activity chain centers as a Multi-Criteria Decision-Making (MCDM) problem. We address the intricacies of contractor selection by integrating MCDM and system thinking approaches, emphasizing the alignment of investment strategies with broader urban development goals. First, a time delay was introduced between the first and second rounds of administering the weighting questionnaire to capture decision-makers’ preferences for the evaluation criteria as System-2 thinking, then the Grey System-2 Thinking (GS2T) weighting method was proposed for group decision-making. Second, the Compromise Ranking of Alternatives from Distance to Ideal Solution (CRADIS) method was incorporated into the Grey Systems Theory (GST), resulting in the development of the Grey-CRADIS method, which was applied to rank seven contractors for constructing activity centers across four urban scenic spots. Using the proposed GS2T with the developed Grey-CRADIS method in conjunction with the decision-makers’ preferences, Company-2 was found to be the best contractor for the construction project. Finally, classical MCDM methods such as theWeighted Sum Model (WSM) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) were employed to confirm the top-ranking contractor.